2019
DOI: 10.1103/physreva.99.063421
|View full text |Cite
|
Sign up to set email alerts
|

Fast and dense magneto-optical traps for strontium

Abstract: We improve the efficiency of sawtooth-wave-adiabatic-passage (SWAP) cooling [1-3] for strontium atoms in three dimensions and combine it with standard narrow-line laser cooling. With this technique, we create strontium magneto-optical traps with 6 × 10 7 bosonic 88 Sr (1 × 10 7 fermionic 87 Sr) atoms at phase-space densities of 2 × 10 −3 (1.4 × 10 −4 ). Our method is simple to implement and is faster and more robust than traditional cooling methods. arXiv:1903.06435v1 [physics.atom-ph]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…After construction and characterization, the assembly was mounted in a stainless steel vacuum chamber attached to the vacuum system [33]. In Fig.…”
Section: Experimental Setup a Crossed Cavitiesmentioning
confidence: 99%
“…After construction and characterization, the assembly was mounted in a stainless steel vacuum chamber attached to the vacuum system [33]. In Fig.…”
Section: Experimental Setup a Crossed Cavitiesmentioning
confidence: 99%
“…The "red" MOT stage operates in two phases. The sawtooth wave adiabatic passage (SWAP) technique [35,36] is applied during an initial broadband phase wherein the laser detuning is swept at a rate of 40 kHz in a triangle waveform from ∆ − /2π = −10 MHz to ∆ + /2π = +200 kHz followed by a lower power, single frequency phase with the detuning fixed at ∆/2π = −290 kHz. At the end of both phases, we capture 5×10 5 atoms on average.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…As was found in Refs. [5][6][7][8][9], SWAP cooling does not achieve a temperature as low as that from Doppler cooling; for the range plotted in Fig. 1, the asymptotic temperature was more than ∼ 10X the Doppler temperature for ev- eryω r .…”
Section: A No Leak B = 0: Steady State Vsωrmentioning
confidence: 99%
“…Finally, as was seen in Refs. [5][6][7][8][9], the simulations showed that the kinetic energy is extracted from the atom much faster using SWAP than using Doppler cooling.…”
Section: A No Leak B = 0: Steady State Vsωrmentioning
confidence: 99%